Strategies to Curbing Corruptive Practices through the Promotion of Accountability and Transparency in the Nigerian Public Service - Isinkaye, Kehinde Abiodun; Ajayi, Olufemi Oladele (NIU Journal of Humanities, 2021)
The need to curb corruptive practices in the Nigeria public service is glaringly clear as it has become enigma that is hard and strong to be uprooted. It is globally known that accountability and transparency are necessary tools to checkmate corruptive practices in public offices, Nigerian public service inclusive. Accountability refers to answerability of  oneâ€™s action or behavior that involves the development of objective standard of evaluation of persons and units within organization, while transparency   denotes a situation when the processes of government are opened and accessed to the people and the more open the process, there more easily enforceable in accountability (Olowu 2015). Efforts to eradicate this pervasive bureaucratic abuses are continuously challenging and paradoxically too, Lack of accountability and transparency breeds corruption in the sense of abuse of public office for personal or private gain (Dibbie, 2014). Indeed, the concern for the eradicating corruption is the Nigeria public life through the promoting accountability and transparency has been demonstrated since the launch  of economic and financial fraud commission (EFFC)) and Independence corrupt practices     (ICPC) by the President Olusegun Obasanjoâ€™s  government The present government has further  internationally the war on corruption eradication by it avowed commitment to prosecuting corrupt public officials  and embarking of external networks such as the prominent participation in the London Government Anti-Corruption Submit in 2016, 30 th Annual submit of the Assembly of the African Union in January 2018 and open government partnership in Paris (      2019). The paper assesses factors that have induced corruptive practices in the Nigerian public service and suggests strategies to ameliorate it, in the nationâ€™s public service and in the nation at large.